VD_FINDINFO HC / 2011 / 364 vom 5. Juli 2011 - VD Tribunal cantonal (2011)
PROTECTION DE L'UNION CONJUGALE, DROIT D'ÊTRE ENTENDU, OBLIGATION D'ENTRETIEN | 176 al. 1 ch. 1 CC, 138 al. 3 let. a CPC (CH)